Performance Analysis of Low-Power Wide-Area Network (LPWAN) as a Low-Power Long-Range Communication Solution in WSN Applications (Karapan Network Journal : Journal Computer Technology and Mobile Ad Hoc Network, 2025)
LPWAN has emerged as a key communication technology that bridges the gap between the need for wide coverage and power efficiency in large-scale WSN implementations. Wireless sensor networks deployed in remote or hard-to-reach locations often face challenges in terms of battery life and data transmission reliability over significant distances. This study analyzes the performance of various LPWAN technologies, such as LoRaWAN, Sigfox, and NB-IoT, in the context of WSN applications that require low-throughput, non-periodic data transmission over kilometers. The performance analysis focuses on three key metrics: power consumption (which determines the battery life of sensor nodes), communication range (the ability to cover a large geographic area), and network capacity (the ability to support a large number of sensor nodes). Comparative results show that each LPWAN technology offers unique trade-offs; for example, LoRaWAN stands out for its independent architecture and excellent receiver sensitivity for extended coverage, while NB-IoT offers seamless integration with existing cellular infrastructure. By identifying the strengths and weaknesses of each solution, this study provides important recommendations for engineers and researchers to select the most suitable LPWAN platform, which optimizes operational durability and cost efficiency for various WSN application scenarios, ranging from environmental monitoring to smart agriculture. The implementation of LPWAN effectively ensures the feasibility of WSN for sustainable long-distance Internet of Things (IoT) projects.
Keywords: LPWAN (Low-Power Wide-Area Network); WSN (Wireless Sensor Network); Power consumption; communication range; LoRaWAN